VISUALISASI GEOMETRI NETRAL BERBASIS AUGMENTED REALITY - Cut Najwa Aulia; Lukman Hakim Laia; Nisa Rahmadani; Fevi Rahmawati Suwanto (Afore : Jurnal Pendidikan Matematika, 2025)
This study was conducted as a Research and Development (R&D) project with the primary objective of developing an Augmented Reality (AR)-based learning medium to support the teaching of three-dimensional geometry for students in the Mathematics Education Study Program. The development process followed the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fourth-semester students at Universitas Negeri Medan. The instruments used in this study included expert validation questionnaires for both content and media, user response questionnaires, and learning outcome tests. The resulting product is an AR-based instructional medium designed for neutral geometry material, specifically intended for fourth-semester mathematics students. Validation results indicate that the developed AR media is highly valid in terms of content quality, visual design, and functional performance. Student responses to the media were overwhelmingly positive, as reflected by indicators such as engagement, ease of use, and increased learning motivation. The effectiveness test demonstrated a significant improvement in student learning outcomes following the use of the AR-based media. Therefore, this Augmented Reality learning tool is considered both feasible and effective for implementation in geometry instruction, offering an innovative alternative to enhance students' conceptual understanding in the field of mathematics.